2016
DOI: 10.4236/odem.2016.43008
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Hazards, Safety and Hygienic Practices among Timber Workers in a South Eastern State, Nigeria

Abstract: Background: Timber workers, especially in developing countries, are faced with challenges of prevention and control of work place hazards and illnesses. Objective: To determine the awareness of occupational hazards, effects, safety and hygienic practices among timber workers in a South Eastern State in Nigeria. Methods: A cross sectional descriptive design that used the total population of timber workers involved in the processing and marketing of wood in three major timber markets in a South Eastern State in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…This is supported by the findings in a study conducted among timber workers in a South-Eastern State in Nigeria, which reported high level of awareness of the hazardous nature of wood dust, and their main source of awareness was from their personal experiences. 18 It is therefore not surprising that whereas less than two-thirds (55.8%) of the respondents in this study had good knowledge of the workplace hazards of sawmill workers, most of them 80.9% had good knowledge of prevention of exposure to the hazards. Studies conducted among sawmill workers in Nigeria and other sub-Saharan African countries majorly reported poor training on occupational health and safety with concomitantly poor knowledge of their workplace hazards.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…This is supported by the findings in a study conducted among timber workers in a South-Eastern State in Nigeria, which reported high level of awareness of the hazardous nature of wood dust, and their main source of awareness was from their personal experiences. 18 It is therefore not surprising that whereas less than two-thirds (55.8%) of the respondents in this study had good knowledge of the workplace hazards of sawmill workers, most of them 80.9% had good knowledge of prevention of exposure to the hazards. Studies conducted among sawmill workers in Nigeria and other sub-Saharan African countries majorly reported poor training on occupational health and safety with concomitantly poor knowledge of their workplace hazards.…”
Section: Discussionmentioning
confidence: 67%
“…Even though, compliance with many of the key safety practices was sub-optimal among the respondents in this study, the levels are relatively higher than those obtained in studies conducted among sawmill workers in other cities across Nigeria. [16][17][18] A study among sawmill workers in Ile-Ife, Nigeria, 16 reported that 72.3 to 79.8% of respondents have never utilized any safety device. Another study among sawmill workers in North-central Nigeria, 17 reported that less than 20% of participants wore protective devices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, knowledge of these interactions between work and health is fundamental in understanding and practice of occupational health and safety, the importance of safety at the workplace is often overlooked. [2][3][4] More than one-third of injuries reported in the hospitality industry are due to trips and falls; making spillages the most common workplace hazard. 5 It is a known fact that different occupations are occupied with different forms of hazard.…”
Section: Introductionmentioning
confidence: 99%